Pemberdayaan Perempuan Melalui Organisasi Fatayat NU Pimpinan Ranting (PR) Rejodadi untuk Mendukung Kemandirian Ibu Rumah Tangga di Dusun Rejodadi - Maslahatul Bariroh; Rivo Nugroho (J+PLUS UNESA, 2026)
Women in rural areas continue to face gender inequality influenced by patriarchal culture and limited access to social and economic opportunities. In the context of the santri community in Rejodadi Hamlet, women are often positioned within the domestic sphere, resulting in limited social participation. Religious-based women’s organizations such as Fatayat NU play a strategic role as a medium of non-formal education in supporting the process of women’s empowerment. This study aims to describe the perspectives of Fatayat NU administrators and members regarding women’s positions, explain the forms of empowerment implemented, and analyze their impact on the independence of housewives. The study employed a descriptive exploratory qualitative approach using non-participant observation, semi-structured interviews, and documentation involving seven informants. The findings reveal that Fatayat NU PR Rejodadi implements empowerment programs in religious, economic, social, and leadership sectors. These programs contribute to the improvement of members’ emotional, intellectual, social, and economic independence. This study demonstrates that women’s religious organizations at the hamlet level can serve as agents of empowerment that strengthen women’s capacities within the culture of santri communities.